MAIYAH MOCOPAT SYAFAAT DALAM PERSPEKTIF PSIKOLOGI - Muhammad Azizul Mustafa (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Abstract: This article describes the mocopat Maiyah Intercession in Psychology perspective. Psychology viewpoint in this article from the perspective of the four major schools of psychology, namely: Psychoanalytic, Behavioristik, Humanistic and Transpersonal. Maiyah mocopat Intercession is a panel of scientific study that is a discussion (sinau together) or sharing on topics of humanity, which teaches the spirit of living with tolerance and live together in kindness contribution. Maiyah which means